Gray-White Matter Blurring of the Temporal Pole Associated With Hippocampal Sclerosis: A Microstructural Study Involving 3 T MRI and Ultrastructural Histopathology. (13th September 2021) - Demerath, T; Donkels, C; Reisert, M; Heers, M; Rau, A; Schröter, N; Schulze-Bonhage, A; Reinacher, P; Scheiwe, C; Shah, M J; Beck, J; Vlachos, A; et al.
Abstract: Hippocampal sclerosis (HS) is often associated with gray-white matter blurring (GMB) of the anterior temporal lobe. In this study, twenty patients with unilateral temporal lobe epilepsy and HS were studied with 3 T MRI including T1 MP2RAGE and DTI/DMI sequences. Anterior temporal lobe white matter T1 relaxation times and diffusion measures were analyzed on the HS side, on the contralateral side, and in 10 normal controls. Resected brain tissue of three patients without GMB and four patients with GMB was evaluated ultrastructurally regarding axon density and diameter, the relation of the axon diameter to the total fiber diameter (G-ratio), and the thickness of the myelin sheath. Hippocampal sclerosis GMB of the anterior temporal lobe was related to prolonged T1 relaxation and axonal loss. A less pronounced reduction in axonal fraction was also found on imaging in GMB-negative temporal poles compared with normal controls. Contralateral values did not differ significantly between patients and normal controls. Reduced axonal density and axonal diameter were histopathologically confirmed in the temporopolar white matter with GMB compared to temporal poles without. These results confirm that GMB can be considered an imaging correlate for disturbed axonal maturation that can be quantified with advanced diffusion imaging.